Putative Extracellular Electron Transfer in Methanogenic Archaea - Gao, Kailin; Lu, Yahai (Frontiers in Microbiology, 2021)
It has been suggested that a few methanogens are capable of extracellular electron transfers. For instance, Methanosarcina barkeri can directly capture electrons from the coexisting microbial cells of other species. Methanothrix harundinacea and Methanosarcina horonobensis retrieve electrons from Geobacter metallireducens via direct interspecies electron transfer (DIET). Recently, Methanobacterium, designated strain YSL, has been found to grow via DIET in the co-culture with Geobacter metallireducens. Methanosarcina acetivorans can perform anaerobic methane oxidation and respiratory growth relying on Fe(III) reduction through the extracellular electron transfer. Methanosarcina mazei is capable of electromethanogenesis under the conditions where electron-transfer mediators like H2 or formate are limited. Additionally, membrane-bound multiheme c-type cytochromes (MHC) and electrically-conductive cellular appendages have been assumed to mediate the extracellular electron transfer in bacteria like Geobacter and Shewanella species. These molecules or structures are rare but have been recently identified in a few methanogens. Here we review the current state of knowledge for the putative extracellular electron transfers in methanogens and highlight the opportunities and challenges for future research.